A Systematic Approach to Develop Level A, In-vitro and In-vivo Correlation (IVIVC)-Ketoprofen BCS Class II Drug Example: In-vitro and In-vivo Correlation of Ketoprofen - Sarfraz, Muhammad; Ahmad, Mahmood; Sarfraz, Attia (Biological Sciences - PJSIR, 2012)